We are mentoring more often: experiences of being a mentor in a training school project - Johan Bäcklund; Rebecka Florin Sädbom; Lena Manderstedt; Helena Anderström (Education Inquiry, 2024)
ABSTRACTIn teacher education mentoring pre-service teachers is a critical factor. With background in research around mentoring pre-service teachers in connection to a training school project, this study aims to contribute knowledge about and identify mentors’ experiences of mentorship in the setting of a training school. Through focus group interviews and semi-structured interviews, foregone by a survey aiming at identifying general views of mentoring, helping to create interview guides, data has been collected for 11 months. Through an interpretative phenomenological analysis, the results show two key themes emerging from mentoring in a training school where the first is strengthening the role as a mentor through three distinct experiences: collegiate learning, structure, and competence development. The second theme, challenging in the role as a mentor, involves four distincttdslevelions of experiences: assessment, planning (linked to the mentoring situation), workload and diversity. The conclusions show that the general experience is positive, but that there are some factors concerning stress and workload; a reworked structure that need to be put into consideration.